Numeracy Literacy Skills and Pancasila Student Profiles through the Implementation of Ethnomathematics-Based STEAM - Kurratul Aini; Abdul Wahab; Muhammad Misbahudholam AR; Asmoni Asmoni (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study investigates the implementation of ethnomathematics-based STEAM learning and its impact on numeracy literacy skills and the Pancasila Student Profile of students at SDN Karangnangka II. The research aims to integrate local cultural values into mathematics education and assess its effectiveness in enhancing students’ numeracy literacy. A mixed-method approach with a sequential exploratory design was used. Data were collected through observations, interviews, and tests. Ethnomathematics elements were identified within Asta Tinggi Sumenep, including its main gate, tomb dome, and landmark, which incorporate various geometric shapes. The learning process followed the steps: Observe, New Idea, Innovation, Creativity, and Society, integrating six dimensions of the Pancasila Student Profile. The implementation of ethnomathematics-based STEAM learning significantly improved students’ numeracy literacy. Pre-test and post-test results showed an increase in average scores from 48.00 to 81.00. Normality tests (Kolmogorov-Smirnov and Shapiro-Wilk) indicated that data were normally distributed (? 0.05). A paired-sample t-test revealed a significant effect (? = 0.001 0.05), confirming the positive impact of this learning model. The findings highlight the effectiveness of integrating local cultural elements into STEAM education. The approach fosters both numeracy literacy and the development of Pancasila Student Profile competencies, aligning education with cultural heritage. Ethnomathematics-based STEAM learning enhances students’ numeracy literacy and character development. Future research should explore its scalability and long-term benefits in broader educational contexts.